1992
DOI: 10.1097/00006254-199202000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postnatal X-Ray Pelvimetry After Caesarean Section in the Management of Subsequent Delivery

Abstract: The purpose of this study was to investigate the influence of postnatal x-ray pelvimetry after caesarean section on the management of the subsequent pregnancy. The case records of 331 women delivered by casearean section in their first pregnancy were reviewed. By standard

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
6

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 4 publications
1
18
0
6
Order By: Relevance
“…There may be a concern for litigation. Other factors that may contribute to increased cesarean section rates after a pelvic fracture include the question of whether pelvic disproportion exists, obstetrician training and experience, and previous results [3,6,9,10,12,14,15,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be a concern for litigation. Other factors that may contribute to increased cesarean section rates after a pelvic fracture include the question of whether pelvic disproportion exists, obstetrician training and experience, and previous results [3,6,9,10,12,14,15,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the obstetric community, there is belief women who have had pelvic fractures cannot deliver vaginally [3,6,10,18]. Many women are not even given a chance for a trial of labor once the obstetrician is aware of the history of pelvic fracture [2].…”
Section: Introductionmentioning
confidence: 99%
“…2-4 Both Krishnamurthy et al 5 (in a retrospective study in 1991) and Thubisi et al 6 (in a prospective randomized study in 1993) reported that x-ray pelvimetry in women with one previous cesarean section increases the the rate of subsequent delivery by cesarean section, and is a poor predictor of the outcome of labor. Nevertheless, technological advances (CT and MRI) offer simplicity, reduction or absence of ionizing radiation, reliability and accuracy.…”
mentioning
confidence: 99%
“…Les études de qualités sont peu nombreuses mais certaines apportent une réponse : tout d'abord l'étude de Krishnamurthy et al [19] qui retrouve un taux identique d'accouchement par voie basse autour de 70 %, que le bassin soit jugé normal ou rétréci (diamètre promontorétropubien [PRP] < 110 mm, diamètre transverse utile [TU] < 115 mm, diamètre biépineux [BE] < 90) sur la radiopelvimétrie réali-sée systématiquement après la césarienne.…”
Section: Pelvimétrieunclassified